tRNA-derived small RNA 3’ tRF-Ala CGC obstructs NK cytotoxicity via cleavage of membrane protein MICA in colorectal cancer - Zhang, Jing; Ou, Chunlin; Li, Xin; Fu, Li; Luo, Qizhi; Wang, Jie; Zou, Yizhou (Frontiers in Immunology, 2025)
BackgroundImmune escape remains a major challenge in cancer immunotherapy. Transfer RNA (tRNA)-derived small RNA (tsRNA) represents a novel class of non-coding RNAs generated from tRNA cleavage, regulating gene expression at transcriptional and translational levels. These tsRNAs exhibit diverse biological functions, including immune modulation, metabolic disorders, and cell death. Despite their critical involvement in tumor progression, the role of tsRNAs in Natural killer (NK) cells related to immune escape within colorectal cancer (CRC) has not been revealed yet.MethodsHigh-throughput sequencing and the tRFexplorer database were utilized to compare the profiles of CRC and normal tissues. Techniques such as RT-qPCR, western blotting, and flow cytometry were employed to assess gene and protein expression. The Cell Counting Kit-8 assay, colony formation assay, and apoptosis analysis were used to evaluate tumor heterogeneity. Differential gene expression between the tRF-3021a inhibitor and negative control (NC) in HCT116 cells was quantified and characterized using RNA sequencing.ResultsWe identified 3’ tRF-AlaCGC (tRF-3021a) as significantly upregulated in CRC tissues. Major histocompatibility complex class I related chain A (MICA) is an important and stress-induced ligand of the natural killer group 2 member D receptor (NKG2D) that is expressed in various cancer cells. MICA undergoes post-translational modifications that regulate their expression as they are called membrane-bound MICA (mMICA) at the cancer cell surface. mMICA is a ligand that induces the activation of NK cells. Proteolytic cleavage of mMICA by A Disintegrin Metalloproteinase Domains (ADAMs) is the underlying mechanism in CRC. Mechanistically, tRF-3021a promotes proteolytic cleavage of mMICA by upregulating ADAM10, generating soluble MICA (sMICA). Elevated sMICA acts as a decoy ligand for NKG2D receptors on NK cells, impairing cytotoxicity and facilitating immune escape. Functional assays confirmed that tRF-3021a knockdown enhances NK cell-mediated CRC cell killing, while overexpression promotes CRC proliferation and inhibits apoptosis. Clinically, tRF-3021a is elevated in CRC tissues, serum exosomes, and cell lines, cleaved by ANG, demonstrating diagnostic potential. In vivo, experiments provided further evidence that inhibition of tRF-3021a reduce tumorigenicity.ConclusionOur findings reveal tRF-3021a as a novel biomarker and therapeutic target for CRC immunotherapy.